Deteksi Kegagalan Pemrosesan Informasi Kognitif(CIP) dalam Pengambilan Keputusan Karier Remaja - ., Amelia; Gunawan, William (Noetic Psychology, 2014)
AbstractThis study aims to detecting the cause of cognitive information processing failure in career decision making on adolescence. As much as 164 adolescence who were in grade 12, either major of science and social class are participate in this study. Career Thought Inventory is used to find the cause of cognitive dysfunction in adolescence. The result show 58 people or 35% subject tend to have problems with their selection of their career. Indication of dominant issues arise in the career decision making on adolescence is caused by External Conflict (EC). Keyword: Cognitive Information Processing; Career Decision Making; Adolescence.